La cura come paradigma di integrazione: recensione a Cura e giustizia. Tra teoria e prassi, volume di Laura Palazzani (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
Laura Palazzani’s project is considerably current in legal and European outline because of her approach to ethical topics. The theoretical knowledge in bioethics answers practical questions through principles that cover up different values. Integration is the model whereby the “just care” can guide life-choices and bioethics items. The match between theory and practice reveals how the Care protects life-actions by ideology of self-interest.
Keywords: Laura Palazzani; care; justice; life-choices; self-interest